Hypothalamic IGF-I Gene Therapy Prolongs Estrous Cyclicity and Protects Ovarian Structure in Middle-Aged Female Rats - Rodríguez, Silvia Susana (2013)
There is substantial evidence that age-related ovarian failure in rats is preceded by abnormal responsiveness of the neuroendocrine axis to estrogen positive feedback. Because IGF-I seems to act as a permissive factor for proper GnRH neuronal response to estrogen positive feedback and considering that the hypothalamic content of IGF-I declines in middle-aged (M-A) rats, we assessed the effectiveness of long-term IGF-I gene therapy in the mediobasal hypothalamus (MBH) of M-A female rats to extend regular cyclicity and preserve ovarian structure. We used 3 groups of M-A rats: 1 group of intact animals and 2 groups injected, at 36.2 weeks of age, in the MBH with either a bicistronic recombinant adeno-associated virus (rAAV) harboring the genes for IGF-I and the red fluorescent protein DsRed2, or a control rAAV expressing only DsRed2. Daily vaginal smears were taken throughout the study, which ended at 49.5 weeks of age. We measured serum levels of reproductive hormones and assessed ovarian histology at the end of the study. Although most of the rats injected with the IGF-I rAAV had, on the average, well-preserved estrous cyclicity as well as a generally normal ovarian histology, the intact and control rAAV groups showed a high percentage of acyclic rats at the end of the study and ovaries with numerous enlarged cysts and scarce corpora lutea. Serum LH was higher and hyperprolactinemia lower in the treated animals. These results suggest that overexpression of IGF-I in the MBH prolongs normal ovarian function in M-A female rats.